Feasibility analysis model for developer-proposed housing projects in the Republic of Korea - Huh, Young-Ki; Hwang, Bon-Gang; Lee, Joong-Seok (Journal of Civil Engineering and Management, 2012)
The current construction industry recession in the republic of Korea has caused many construction companies to promote their own housing development projects. However, developers are still proposing many housing projects. While many studies on feasibility analysis for housing projects have been released, the focus was on economic feasibility, and factors related to developers have not been identified clearly enough to be used in practice. A feasibility analysis model is developed for apartment development projects in Korea to help main contractors make sound decisions on projects proposed by developers. To establish the model, 31 driving factors behind projects’ success, in seven categories, were identified through several meetings with experts and surveys. Factors such as ‘developer’, ‘method of raising funds’ and ‘method of contract’, which were considered less important in previous studies, were included in the model. Criteria for each factor were also developed to assess the factors quantitatively. Then, each factor was assigned a weight by applying the Analytic Hierarchy Process. ‘Salability’, ‘economic feasibility’, ‘site location’ and ‘method of raising funds’ have relatively high weights. Finally, based on a Monte Carlo simulation, a feasibility analysis model was established, providing a probability distribution of each project’s grade. The model was applied to 12 housing projects constructed in Busan (seven successful projects and five abandoned projects) to verify its reliability. The application results showed that the model properly filtered projects that are unlikely to be profitable, indicating that it is reasonably reliable. Our model could thus be a useful tool for contractors, especially those with limited experience in analyzing project development feasibility.